Identification of optimal bamboo fiber content to enhance impact resistance of reinforced concrete - Aditama, Vega; Dewi, Sri Murni; Wibowo, Ari; Wijaya, Ming Narto (Eastern-European Journal of Enterprise Technologies, 2025)
This research focuses on the impact resistance of reinforced concrete enhanced with bamboo fibers, aiming to evaluate the influence of varying bamboo fiber content on impact energy, deflection, and impact force. Reinforced concrete beams were prepared with bamboo fiber contents of 1.25%, 2.5%, and 3.75%, representing a range of low to high volume fractions. The primary objective was to examine how bamboo fiber addition improves the concrete’s mechanical performance under repeated impact loads and to determine the optimal fiber dosage for structural efficiency. The results indicate that the incorporation of bamboo fibers significantly reduces both maximum deflection and peak impact force. Notably, the 1.25% fiber content exhibited the highest increase in the Toughness Modulus (MoT), reflecting superior energy absorption capacity. Conversely, higher fiber contents (2.5% and 3.75%) led to a noticeable decline in MoT values, likely due to poor fiber dispersion and agglomeration effects. Graphical analysis of polynomial regression curves revealed that although bamboo fiber generally enhances energy absorption, each energy parameter exhibits a different trend. Released energy shows a moderately increasing trend with higher fiber content, but with high variability at elevated percentages, indicating inconsistency. Absorbed energy displays minor and inconsistent fluctuations across all fiber contents, suggesting limited fiber influence. In contrast, deformation energy peaked at 1.25% fiber content and declined sharply beyond 2.5%, implying that excessive fiber reduces the material’s deformation ability. These findings confirm that bamboo fibers are a viable, sustainable additive to improve the impact resistance of concrete